Compact, cost-efficient microfluidics-based stopped-flow device - Bleul, Regina; Ritzi-Lehnert, Marion; Höth, Julian; Scharpfenecker, Nico; Frese, Ines; Düchs, Dominik; Brunklaus, Sabine; Hansen-Hagge, Thomas; Meyer-Almes, Franz-Josef; Drese, Klaus S. (Analytical and bioanalytical chemistry)
Stopped-flow technology is frequently used to monitor rapid (bio)chemical reactions with high temporal resolution, e.g., in dynamic investigations of enzyme reactions, protein interactions, or molecular transport mechanisms. However, conventional stopped-flow devices are often overly complex, voluminous, or costly. Moreover, excessive amounts of sample are often wasted owing to inefficient designs. To address these shortcomings, we propose a stopped-flow system based on microfluidic design principles. Our simple and cost-efficient approach offers distinct advantages over existing technology. In particular, the use of injection-molded disposable microfluidic chips minimizes required sample volumes and associated costs, simplifies handling, and prevents adverse cross-contamination effects. The cost of the system developed is reduced by an order of magnitude compared with the cost of commercial systems. The system contains a high-precision valve system for fluid control and features automated data acquisition capability with high temporal resolution. Analyses with two well-established reaction kinetics yielded a dead time of approximately 8-9 ms.